Vivipary in Kaempferia parviflora Wall. Ex-Baker: discovery and utilization - Devi, Akoijam Ranjita; Raj, N. Mini; Minimol, J.S (Journal of Tropical Agriculture, 2023)
Kaempferia parviflora, popularly known as Black ginger, belongs to the family Zingiberaceae. Its rhizomes are widely used as an aphrodisiac, apart from other uses. This experiment carried out at Kerala Agricultural University, Thrissur, Kerala, India, reports for the first time the phenomenon of vivipary in K. parviflora. Growth and development of viviparous seedlings after transplanting showed positive results, and rhizome formation was noticed in one season. In the first season, mini rhizomes were used as seed for raising fresh crop and its growth was compared with normal rhizome grown plants. Even though the rhizome yield of the viviparous plants was 30 per cent lower than normal plants, vivipary can be an alternate option for the natural regeneration/propagation of this valuable medicinal plant.